An Underestimated Diagnosis in Practice: Wernicke Encephalopathy in Two Patients With Cancer - (:unkn) unknown (JOURNAL NEUROLOGICAL SCIENCES, 2017)
Impairment of mental status is frequently seen in cancer patients. Common causes are infection, metabolic disturbance, organ failure, medication, delirium or metastatic disease. Wernicke encephalopathy (WE) is likely to be underestimated in clinical practice in nonalcoholic population including this special patient group. The purpose of this paper is to take attention to WE and cancer concomitance, and emphasize the role of magnetic resonance imaging (MRI) in the early diagnosis of this complicated disease. We report two cancer patients who were consulted to our neurology department because of altered mental status and other neurological disabilities. When the patients underwent brain MRI for differential diagnosis, symmetrical perimidline lesions of the brain made the suspicion of WE diagnosis. In addition, one of the patient's MRI showed symmetric cortical and cerebellar involvement that is more typical in nonalcoholic form of WE. Both patients mostly recovered clinically, also showed concordant resolution of MRI abnormalities within 4-8 weeks after thiamine supplementation. WE diagnose should be kept in mind in cancer patients with altered mental status and thiamine treatment should be started during undergoing evaluation and differential diagnose to prevent irreversible clinical sequelae. Improved recognition of radiologists and well-known imaging findings of WE can facilitate early detection and effective treatment in nonalcoholic WE patients.
Keywords: Wernicke encephalopathy; thiamine deficiency; Wernicke encephalopathy in malignancy